"Life will go on with the beauty of the roses": The moral dimensions of coping with distress through autobiographical writing during Covid-19 - Nia C. Parson; Heather M. Wurtz; Meghan Lowrey; Cit'Clatli Santos (Elsevier, 2022)
This article is based on our analysis of a subset of data from the Pandemic Journaling Project-Phase 1 (PJP-1). The PJP, a collective, on-line journaling platform, was co-founded by anthropologists Dr. Sarah S. Willen and Dr. Katherine A. Mason in 2020. It has provided individuals with dedicated anonymous and confidential space to document and share their lived experiences of the Covid-19 pandemic over time (May 2020-May 2022). We employ a case study approach to closely analyze the journal entries of one Guatemalan woman, whom we call Crescencia, from our broader sample of 50 participants writing from within Latin America. Our analysis suggests that the PJP-1 platform provided a valuable space for Crescencia to cope with the distress of Covid-19 by fostering practices of self-reflection and social connectedness. We assert that the process of collective and anonymous online journaling through a platform like PJP-1 may not only provide space for some people to strengthen their sense of agency despite the uncontrollable conditions of crisis, but may also constitute an informal network of care through the sharing and preservation of one's experiences during the pandemic. Our findings point to the potential of PJP-type platforms in psychosocial interventions and mental health care practice to support individuals, families, and communities coping with hardship and trauma, which may be a particularly effective approach in resource-poor contexts where mental health care is scarce or stigmatized. PJP-1 may also provide a valuable model for future research approaches to understanding coping and resilience in similar conditions where in-person, in vivo research may not be viable, such as during armed conflict or the aftermath of environmental disaster.